Application of modern information technologies of feedback in impact martial art on the example of taecwondo WTF - Epov, G. O.; Kalinin, M. E.; Epov, O. E.; Panikov, V. E.; Potapova, A. K. (European Journal of Physical Education and Sport Science, 2022)
The article deals with topical issues related to the use of feedback information technologies. Since there are not so many studies on this topic, the review includes information on the example of other sports where research is already being carried out, as well as preliminary own research obtained on the example of athletes of percussion martial arts, taekwondo WTF. The study examines the main parameters of the kinematics of the movement of athletes, the study of which allows us to evaluate their effectiveness, and the magnitude of the impact, primarily when assessing the external side of the load. Feedback information technologies for continuous monitoring of motor activity are currently informative, reliable tools in the work of coaches, the information from which helps to plan the training process and carry out the continuous process of training an athlete both in different periods of the annual cycle and during the recovery period.